Pricing Irrigation Water : A Literature Survey - Johansson, Robert C. (World Bank, Washington, DC, 2014)
As water scarcity and population pressures increase, more countries are adopting water pricing mechanisms, as their primary means of regulating the consumption of irrigation water. The way to allocate water efficiently is to "get the prices right", but how to accomplish this is open to debate. Water pricing methods are sensitive to the social, physical, institutional, and political setting. To assess the costs and benefits of a particular irrigation project, the pricing method must be tailored to local circumstances. The author's survey of the resource economics literature on irrigation services and pricing, will be useful for developing comprehensive guidelines for water policy practitioners. He synthesizes accumulated knowledge about the implementation, and performance of various water pricing methods used over the past two decades: volumetric pricing (marginal cost pricing), output and input pricing, per area pricing, tiered pricing, two part tariffs, and water markets. As water scarcity and population pressures increase, more countries are adopting water pricing mechanisms as their primary means of regulating the consumption of irrigation water. The way to allocate water efficiently is to "get the prices right", but how to accomplish this is open to debate. Water pricing methods are sensitive to the social, physical, institutional, and political setting. To assess the costs and benefits of a particular irrigation project, the pricing method must be tailored to local circumstances. The author's survey of the resource economics literature on irrigation services and pricing, will be useful for developing comprehensive guidelines for water policy practitioners. He synthesizes accumulated knowledge about the implementation, and performance of various water pricing methods used over the past two decades: volumetric pricing (marginal cost pricing), output and input pricing, per area pricing, tiered pricing, two part tariffs, and water markets.